Multiscale Characterization of Erosion of TA2 Titanium Alloy Welded Joints - Liu, Ran; Liu, Yingshuang; Zhang, Dalei (Frontiers in Materials, 2022)
Abstract: To prolong the service time of ship and seawater piping systems, titanium alloys have a series of excellent properties, such as their low density, high strength, and seawater corrosion resistance, and it has become the main material used in ocean engineering. A welded joint is a nonuniform structure that is composed of a weld seam (WM), base metal (BM), and heat affected zone (HAZ). When an alloy is used, it is easier to form galvanic corrosion, stress corrosion, and pitting corrosion in a weld joint than when a single metal is used. Therefore, corrosion failure often occurs at a welded joint. In this paper, classical electrochemical testing (EIS, Tafel) and surface morphology analysis (SEM, EDS) were used to study a welded joint, and microarray electrode (WBE) testing was added for the first time to study a welded joint. The corrosion behaviour of each zone of a TA2 titanium alloy welded joint in flowing seawater and the overall corrosion tendency after coupling of three zones were studied at the macro- and submicroscales. Macroscopic results show that the HAZ and BM of a titanium alloy welded joint have better corrosion resistance in seawater. The microarray electrode shows that the WM is the main anode that accelerates corrosion, and at high flow rate, the electrode will change into the cathode. In conclusion, the data in this paper provide a theoretical basis for the corrosion failure mechanism of TA2 welded joints.